A UML extension to specify model refinements - Correa, Natalia; Giandini, Roxana Silvia (2006)
The refinement technique allows us to capture the relationship between specification and implementation in software developments. The precise documentation of the refinement relationship makes it possible to trace the requirements through the refinement steps. Unfortunately, the standard modeling language UML suffers from a lack of notation to specify refinements in a precise way; in particular, compound refinements can be only partially specified, weakening the traceability potential. In this article , we present an extension of UML to express complex model refinements by means of a well defined composition of elementary refinements. Such extension includes an optional notation to specify complex refinements in an accurate and complete way, thus improving the traceability process. Keywords: Software Engineering, Modelling Languages, Model Refinements, UML Extension.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 7 nov. 2008)
CLEI 2006.
Keywords: MODELADO DE SOFTWARE; REFINAMIENTO DE PROGRAMAS; PROCESO DE DESARROLLO DE SOFTWARE; TÉCNICAS DE ESPECIFICACIÓN; UML